2005
DOI: 10.1128/aem.71.7.3575-3580.2005
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Abundance of Total and Pathogenic Vibrio parahaemolyticus Bacteria in Oysters along the Southwest Coast of India

Abstract: The seasonal abundance of Vibrio parahaemolyticus in oysters from two estuaries along the southwest coast of India was studied by colony hybridization using nonradioactive labeled oligonucleotide probes. The density of total V. parahaemolyticus bacteria was determined using a probe binding to the tlh (thermolabile hemolysin) gene, and the density of pathogenic V. parahaemolyticus bacteria was determined by using a probe binding to the tdh (thermostable direct hemolysin) gene. Furthermore, the prevalence of V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
5
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 35 publications
11
125
5
5
Order By: Relevance
“…High concentration and prolonged survival of pathogenic bacteria in sediments from the study area coupled with the filter feeding nature of the shellfishes pose direct or indirect health risk through the consumption of contaminated shellfish. Shellfish associated food borne illness has been reported from India and other Asian countries (Deepanjali et al, 2005). The results of the present study are of particular significance to public health because Vembanadu Lake is the life line of the people in that area as they use this water body for agriculture, fishing, transport and contact recreation.…”
Section: Survival In Sediments With Different Particle Size and Organmentioning
confidence: 76%
“…High concentration and prolonged survival of pathogenic bacteria in sediments from the study area coupled with the filter feeding nature of the shellfishes pose direct or indirect health risk through the consumption of contaminated shellfish. Shellfish associated food borne illness has been reported from India and other Asian countries (Deepanjali et al, 2005). The results of the present study are of particular significance to public health because Vembanadu Lake is the life line of the people in that area as they use this water body for agriculture, fishing, transport and contact recreation.…”
Section: Survival In Sediments With Different Particle Size and Organmentioning
confidence: 76%
“…The tdh gene was detected in four strains, and trh was detected in 23 strains (Figure 2). Several studies have suggested a strong influence of temperature on the concentration of vibrio in marine waters [27][28][29][30] . However, this study only established a correlation with V. vulnifi cus (p < 0.05).…”
Section: Seawater Parametersmentioning
confidence: 99%
“…It has been demonstrated that around 3-6% of V. parahaemolyticus isolated from the environment carry the virulence genes (tdh or trh) 7,8 . Thus it is not easy to isolate tdh + and/or trh + strains from seafood.…”
Section: Discussionmentioning
confidence: 99%
“…These haemolysins are encoded by the tdh and trh genes, respectively; either tdh, trh or both genes are present in most clinical isolates of V. parahaemolyticus 6 . However, only 3-6% of environmental isolates harbour these genes 7,8 . A classification based on combination of the serotypes of two antigens, somatic O and capsular-like K, have been established using clinical strains and serves as a useful tool in epidemiological investigations 9 .…”
Section: Introductionmentioning
confidence: 99%